PENGARUH KUALITAS PRODUK, HARGA DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN AIR MINUM DALAM KEMASAN MEREK AQUA DI KELURAHAN PABUARAN BOGOR - Hari Subagyo, Wawan; Chairunisha Febriana, Ranti (Sekolah Tinggi Ilmu Ekonomi Dewantara, 2020)
This research aims to determine the influence of variable product quality, price and brand image partial and simultaneous to the variable purchase decision of bottled drinking water of Aqua brand in the village of Pabuaran Bogor, as well as knowing the effect of independent variables on the dependent variable. The samples in this study were 97 people. Data analysis techniques use multiple linear regression. T test result showed the product quality variable (X1) and brand image (X3) partially influential for the purchase decision of bottled drinking water (AMDK) Aqua brand in the village of Pabuaran Bogor. It is based on the calculated t count value of two variables greater than t table and the Signification value (p value) is less than 0.1. Variable price (X2) partial has no significant effect on the variable purchase decision of bottled drinking water (AMDK) Aqua brand in the village of Pabuaran Bogor. F test results indicate product quality variables, prices, and brand image simultaneously affect the variable purchase decision of bottled drinking water (AMDK) Aqua brand in the village Pabuaran Bogor. This can be seen that the value F count 6.80 is greater than the F table 2.70 and the significance (0.0) value is smaller than 0.1. The result of the coefficient of determination of 15.3% showed the influence of independent variables, such asproduct quality, price, brand image of the purchase decision variable. The remaining 84.7% is influenced by other variables not included in this study.